The relationships between life skills and post-graduation employment for top college student wrestlers in Japan - Shimizu, S.; Shimamoto, K.; Tsuchiya, H. (International Journal of Sport & Health Science, 2015)
The purpose of this study was to investigate the relationships between life skills and post-graduation employment for top college student athletes. In March 2011, 24 Japanese top level male wrestlers (mean age=22.0±0.2) who had graduated from university in March 2011 answered to the Appraisal Scale of Required Life Skills for College Student Athletes (Shimamoto et al., 2013). This scale has following 10 subscales: stress management, setting goals, thinking carefully, appreciating others, communicating, maintaining etiquette and manners, always making one's best effort, taking responsibility for one's own behavior, being humble, and maintaining physical health and well-being. The relationships between life skills acquisition level assessed in March 2011 and employment situations (employed or unemployed) by March 2012 were examined with nine members who had not obtained employment by the time of graduation from university. The analysis results showed that the employment group (n=4) who had acquired employment within one year of graduation indicated a higher acquisition level compared to the unemployed group (n=5) with regard to setting goals (p<.05). Therefore, it was suggested that there is the positive relationship between setting goals and post-graduation employment for top college student wrestlers.